Politik Hukum dalam Penguatan Integritas Kejaksaan Republik Indonesia Sebagai Pilar Penegakan Hukum yang Berkeadilan - Yudha Aditya Pradana; Ariawan Gunadi (CV Rewang Rencang, 2024)
Integrity is a fundamental pillar in enforcing just law. As a law enforcement agency that has a strategic role in maintaining the supremacy of law and justice in Indonesia, the Attorney General's Office of the Republic of Indonesia is required to always maintain professionalism and integrity in all its duties and authorities. The problem faced in this study is how the legal policy is applied in strengthening the integrity of the Attorney General's Office of the Republic of Indonesia as a pillar of just law enforcement and the right strategy and policy in strengthening the integrity of the Attorney General's Office of the Republic of Indonesia so that it plays an optimal role in enforcing just law. The research method used is normative juridical legal research sourced from secondary data. The results of the study indicate that the legal policy applied in strengthening the integrity of the Attorney General's Office of the Republic of Indonesia aims to make the Attorney General's Office the main pillar in enforcing just law and through the implementation of the right legal policy, the integrity of the attorney's office can be strengthened so that the role of the attorney's office in realizing legal justice can be more optimal and reliable. The right strategy and policy in strengthening the integrity of the Attorney General's Office of the Republic of Indonesia is needed so that the Attorney General's Office can play an optimal role in realizing just law enforcement. With effective strategies and policies, the Prosecutor's Office can improve professionalism, accountability, and transparency in carrying out law enforcement duties.